The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1806-37132008000700011
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento supervisionado em pacientes portadores de tuberculose utilizando supervisores domiciliares em Vitória, Brasil

Abstract: Objective: To evaluate the use of family members as supervisors of directly observed therapy (DOT) in patients with tuberculosis. Methods: This was a prospective descriptive study involving patients diagnosed with pulmonary tuberculosis. The sample comprised 98 patients. A standardized protocol was implemented in order to train the patient and their families. After the training, the patient was allowed to choose either a family member or a health care worker as a supervisor. Absolute and relative frequencies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
0
10
1
12
Order By: Relevance
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 66%
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 66%
“…These flaws result in delayed diagnoses and represent obstacles to program success, and they also favor the risk of TB transmission at the occupational level (31)(32)(33) . Nevertheless, nurses did not report as problematic the centralization of activities or the lack of autonomy of the local units.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à escolaridade, os dois grupos se concentraram principalmente no nível de Ensino Fundamental, o que revela o baixo nível de escolaridade dos pacientes estudados, confirmando a tendência secular da doença, cuja incidência é maior em populações mais desfavorecidas (11) . A distribuição dos pacientes nos dois grupos investigados na presente pesquisa, com relação à faixa etária, esteve entre 16 e 59 anos, estando de acordo com outros estudos (11,12) e se assemelhando com a realidade brasileira, em que a TB atinge principalmente a população economicamente ativa (11) , conferindo significado social à doença.…”
Section: Discussionunclassified